Development of Statistical Habits of Mind Instruments in Teacher Prospective Students - Hayati, Laila; Subarinah, Sri; Prayitno, Sudi; Arjudin, Arjudin (Universitas Tanjungpura, 2024)
Statistical habits of mind (SHOM) is a habit of mind needed to understand, analyze, and interpret data effectively. This research aims to develop an instrument in the affective aspect of measuring SHOM that is valid and reliable. The results showed that the SHOM instrument developed consisted of five faktorons, namely 1) Context of Data, 2) Intuition, 3) Inquiry, 4) Skeptical and Careful, and 5) Thinking Beyond the Textbook. Based on the factor analysis results, it was found that the SHOM instrument is content-valid and reliable but not yet construct-valid. This is indicated by the number of factors formed (13 factors) does not match the number of factors planned in the preparation of the instrument (5 factors), and there are 6 items that have insufficient factor loading values.